The Adrenocortical Function Studies in Children - Iwao Takakura (Paediatrica Indonesiana, 1975)
The recent advances in the laboratory procedures make it possible to study endocrinological states in children more easily and more accurately even in the neonatal period. The successes in purification and the determination of chemical structures of various hormones and their releasing factors make it possible to carry out various loading tests. The progress in the measurement of various hormones and their metabolites especially in the field of radioimmunoassay is really remarkable.If we took adrenocortical function studies as an example, urinary 17 hydroxycorticosteroid was the only reliable item about ten years ago, then plasma 17-OHCS determination using Porter-Silver chromogen was introduced followed by plasma 11-OHCS determination with fluorescence spectrophotometry. Then, cortisol production rate determination became possible using radio-isotope dilution technique, and at present, plasma cortisol can be measured directly with protein competitive radio-immunoassay. Thus, the adrenocortical function studies in the pediatric age group has become easier and more reliable. The author likes to present some endocrinological results in children using various methods and now they can be applied in the clinical work.